Pengaruh Kompensasi, Motivasi dan Kepuasan Kerja Terhadap Turnover Intention Karyawan - Agustini Agustini (Economics and Digital Business Review, 2024)
The investigation was carried out at the Makassar branch of PT Go-Jek Indonesia, an Indonesian technology business specializing in app-based online transportation services. This study examines the impact of compensation, motivation, and job satisfaction on employee turnover intention at PT Go-Jek Indonesia Branch Makassar. The population under study is PT Go-Jek Indonesia Branch Makassar, an Indonesian technology company that operates online transportation in Makassar through mobile applications. The sample for this study was acquired by Random Sampling, adhering to preset criteria. The resulting sample consisted of 21 employees. The study employed statistical techniques, including multiple linear analysis, classical assumption tests, hypothesis testing, and coefficient of determination tests. The findings of this study suggest that Compensation, Motivation, and Job Satisfaction do not impact the employees' intention to leave their positions at PT Go-Jek Indonesia Branch Makassar.